123 Patient Perspectives Regarding Ethics of Neuromodulators in the Treatment of Persistent Postoperative Neuropathic Pain. (August 2016) - Samuel, Nardin; Kalia, Suneil Kumar; Bernstein, Mark A.; Shamji, Mohammed F.
Abstract : INTRODUCTION: The aim of this study is to better understand patients' perspectives of persistent postoperative neuropathic pain (PPNP) and assess perceptions of the ethical issues surrounding implantation of neuromodulators, such as spinal cord stimulators (SCS), to treat PPNP in medically refractory patients. METHODS: Semistructured face-to-face interviews were conducted with patients from the neurosurgery clinics at Toronto Western Hospital. Interviews were audio recorded, transcribed, and subjected to thematic analysis using open and axial coding. RESULTS: The median age of the 18 study participants is 58 years and 44.4% (8/18) were female. The range of the duration of preoperative symptoms varied from 1 month to over 20 years, and was primarily back dominant (11/18). The median time since patients most recently underwent spinal surgery was 3 years. The majority of patients would be willing to have their surgeon reoperate on them if needed, citing a strong patient-physician relationship as the reason for this. Finally, nearly unanimously (17/18), patients did not perceive an ethical problem with a surgeon performing a structurally corrective spinal surgery and subsequently also implanting a SCS in the same patient that develops medically refractory PPNP. Broadly, patients cite trust in the surgeon and confidence in his or her competence as the most important factors in this perspective. CONCLUSION: The results of this work reveal that patients are comfortable with surgeons addressing their pain with all of the tools in their armamentarium, so long as they are well appraised of surgical risks and benefits and have open communication and trust in the physician-patient relationship.